Effectiveness of E-Learning Media to Improve Learning Outcomes Natural Science in Primary Schools - Ariesta, Freddy Widya (LPPM Undiksha, 2019)
This study aims to determine the effectiveness of the application of e-learning media in science lessons on the learning outcomes of fourth-grade students in primary school. Experimental research was conducted for four weeks with learning using e-learning media as an experimental group (n = 32) and using book-based learning as a control group (n = 30). This study used a quasi-experimental method with a pre-test and post- test control group design. The research instrument was taken from observations and scores on student learning outcomes. The data were analyzed using quantitative statistical tests. Based on the data, the researchers know that a teacher plays an important role in developing student learning media through ICT-based e-learning learning design. Also, the results of the study based on the Mann-Whitney N-gain score of students' comprehension ability obtained a significance value of 0.00 <? = 0.05. So that H0 was rejected. This result shows that the ability of students to understand science using e-learning media is significantly better than students who get book-based learning.